2009
DOI: 10.1891/0739-6686.27.243
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cessation Interventions in Cancer Care: Opportunities for Oncology Nurses and Nurse Scientists

Abstract: Smoking cessation is essential after the diagnosis of cancer to improve clinical outcomes. The purpose of this chapter is to provide a systematic review of research on smoking cessation in the context of cancer care with an emphasis on nursing contributions to the field. Data sources included research reports of smoking cessation interventions conducted in people with cancer. Nineteen primary studies were reviewed. High intensity interventions, targeting multiple behaviors, and/or using a multicomponent interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 53 publications
1
44
0
Order By: Relevance
“…Ten RCTs 5,15,16,[66][67][68][69][70][71][72] and 3 PC studies 21,73,74 met the inclusion criteria (Figure 1).…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten RCTs 5,15,16,[66][67][68][69][70][71][72] and 3 PC studies 21,73,74 met the inclusion criteria (Figure 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…Studies were evaluated in 2 groups based on follow-up duration. The group with the shorter follow-up period (n = 6) had a mean follow-up of 5 weeks, 15,21,66,[68][69][70][71][72][73][74] and the longer follow-up group (n = 7) was followed for at least 6 months. 4,5,16,67 In the second group, pooled rates were calculated from the 6-month abstinence rates in all studies except 1, 4 which reported a 12-month rate ( Table 4).…”
Section: Tobacco Cessation Rates and Follow-upmentioning
confidence: 99%
“…11,34,52–57 A table of studies evaluating smoking cessation interventions in cancer patients can be found in an article by Cooley and colleagues. 58 A review of the evidence follows.…”
Section: What Is the Evidence For Smoking Cessation Interventions Amomentioning
confidence: 99%
“…Unfortunately, 15.1% of all cancer survivors report being current smokers [3]. At the time of diagnosis, estimated rates on the prevalence of current smoking vary greatly ranging from approximately 45–75% depending upon a number of factors including type of cancer [4]. For instance, continued smoking appears higher among patients diagnosed with tobacco-related cancers (27%) compared to other cancer survivors (16%) [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, some smokers may be unable or unwilling to quit. Unfortunately, the few clinical interventions conducted have failed to produce significant outcomes [4, 30–35]. For those who continue to smoke following diagnosis, at least two interpretations are possible.…”
Section: Introductionmentioning
confidence: 99%